Conductive electrospun scaffolds with electrical stimulation for neural differentiation of conjunctiva mesenchymal stem cells. Issue 8 (27th February 2019) - Rahmani, Ali; Nadri, Samad; Kazemi, Habib Sayed; Mortazavi, Yousef; Sojoodi, Mahdi
Abstract: An electrical stimulus is a new approach to neural differentiation of stem cells. In this work, the neural differentiation of conjunctiva mesenchymal stem cells (CJMSCs) on a new 3D conductive fibrous scaffold of silk fibroin (SF) and reduced graphene oxide (rGo) were examined. rGo (3.5% w/w) was dispersed in SF‐acid formic solution (10% w/v) and conductive nanofibrous scaffold was fabricated using the electrospinning method. SEM and TEM microscopies were used for fibrous scaffold characterization. CJMSCs were cultured on the scaffold and 2 electrical impulse models (Current 1:115 V/m, 100‐Hz frequency and current 2:115 v/m voltages, 0.1‐Hz frequency) were applied for 7 days. Also, the effect of the fibrous scaffold and electrical impulses on cell viability and neural gene expression were examined using MTT assay and qPCR analysis. Fibrous scaffold with the 220 ± 20 nm diameter and good dispersion of graphene nanosheets at the surface of nanofibers were fabricated. The MTT result showed the viability of cells on the scaffold, with current 2 lower than current 1. qPCR analysis confirmed that the expression of β‐tubulin (2.4‐fold P  ≤ 0.026), MAP‐2 (1.48‐fold; P  ≤ 0.03), and nestin (1.5‐fold; P  ≤ 0.03) genes were higher in CJMSCs on conductive scaffold with 100‐Hz frequency compared to 0.1‐Hz frequency. Collectively, we proposed that SF‐rGo fibrous scaffolds, as a new conductive fibrous scaffold with electrical stimulation are good strategies for neural differentiation of stem cells and the type of electrical pulses has an influence on neural differentiation and proliferation of CJMSCs.